Development of C-Arylcalix[4]resorcinarenes and C-Arylcalix[4]pyrogallolarenes as Antioxidant and UV-B Protector - Jumina Jumina; Dwi Siswanta; Abdul Karim Zulkarnain; Sugeng Triono; Priatmoko Priatmoko; Emmy Yuanita; Nela Fatmasari; Ikhsan Nursalim (Universitas Gadjah Mada, 2019)
Indonesia is rich with essential oils such as anise and clove leave oils. In respect to explore the potential utilization of these resources, it has been conducted the transformation of p-hydroxybenzaldehyde and vanillin (4-hydroxy-3-methoxy benzaldehyde) respectively derived from anise oil and clove leaves oil to a series of C-arylcalix[4]resorcinarenes and C-arylcalix[4]pyrogallolarene macrocycles. Treatment of these aldehydes with resorcinol in the presence of HCl in absolute ethanol at reflux for 8 h afforded C-4-hydroxyphenylcalix[4]resorcinarene (3a) and C-4-hydroxy-3-methoxy phenyl-calix[4]resorcinarene (3b) in good yields. When the aldehydes were treated with pyrogallol under the similar condition, the products were C-4-hydroxyphenyl calix[4]pyrogallolarene (3c) and C-4-hydroxy-3-methoxyphenylcalix[4]pyrogallolarene (3d) which were also obtained in excellent yields. Treatment of these calix[4]resorcinarenes and calix[4]pyrogallolarenes with cinnamoyl chloride and benzoyl chloride in pyridine afforded the corresponding cinnamate esters and benzoate esters in high yields. The resulted C-arylcalix-[4]resorcinarenes and C-arylcalix[4]pyrogallol arenes were subjected to antioxidant activity test using DPPH method and showed strong activity with IC50 values of 15–80 μg/mL. In terms of the synthesized calix cinnamates, the compounds showed UV-B absorption with SPF values of 15–30 at a concentration of 25 ppm which demonstrate their potential to be applied as a UV-B protector. Furthermore, these compounds were also tested for their photostability on the UV-B region and the results showed that the compounds were still unstable under irradiation for 30 min.